2010
DOI: 10.1677/erc-10-0179
|View full text |Cite
|
Sign up to set email alerts
|

The orphan nuclear receptor LRH-1 promotes breast cancer motility and invasion

Abstract: The orphan nuclear receptor liver receptor homologue-1 (LRH-1) has roles in the development, cholesterol and bile acid homeostasis, and steroidogenesis. It also enhances proliferation and cell cycle progression of cancer cells. In breast cancer, LRH-1 expression is associated with invasive breast cancer; positively correlates with ERa status and aromatase activity; and promotes oestrogen-dependent cell proliferation. However, the mechanism of action of LRH-1 in breast cancer epithelial cells is still not clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 47 publications
3
74
0
Order By: Relevance
“…Interestingly, NTF3 has also been shown to increase resistance to anoikis (33). LRH-1 as well has recently been implicated in pancreatic-cancer metastasis and breast-cancer development; these findings may demonstrate similar molecular underpinnings between cancer metastases (14,34,35). Another Rho member in our dataset that promotes metastasis in gastroenterological cancers is semaphorin 5A.…”
Section: Antiproliferative Mechanism Of Lrh-1 Inhibition Is Conservedsupporting
confidence: 52%
“…Interestingly, NTF3 has also been shown to increase resistance to anoikis (33). LRH-1 as well has recently been implicated in pancreatic-cancer metastasis and breast-cancer development; these findings may demonstrate similar molecular underpinnings between cancer metastases (14,34,35). Another Rho member in our dataset that promotes metastasis in gastroenterological cancers is semaphorin 5A.…”
Section: Antiproliferative Mechanism Of Lrh-1 Inhibition Is Conservedsupporting
confidence: 52%
“…Further work will be required to establish the mechanism responsible for this cooperation. Despite this close link between LRH-1 and ERa, it was also found that LRH-1 is expressed in ERa-negative breast cancer cells in which it controlled cell migration and invasion (20,49), suggesting that LRH-1 may also have an important role in hormone-independent cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, LRH-1 is highly expressed and localized in the epithelial compartment of both invasive ductal carcinoma and ductal carcinoma in situ (18,19). Interestingly, depletion of LRH-1 in breast cancer cells decreases cell mobility, invasion and colony formation (20). Moreover, an important crosstalk seems to exist in estrogendependent breast cancer cells, in which LRH-1 is itself regulated by ERa (18).…”
Section: Introductionmentioning
confidence: 99%
“…Simpson and coworkers first reported high expression of LRH-1 in preadipocytes, and they associated LRH-1 expression with transcriptional activation of CYP19 (Clyne et al, 2002). In addition to aromatase regulation, LRH-1 was shown to contribute to cancer progression by promoting motility and cell invasiveness of estrogen receptor (ER)-positive and ER-negative breast cancer cell lines (Chand et al, 2010).…”
Section: Introductionmentioning
confidence: 99%